Research Gaps in Labour Market and Labour Force Information - Schonning, Gil (Relations industrielles / Industrial Relations, 1964)
The purpose of the following paper is to point out some research gaps in labour market and labour force information. At the same time, the author outlines some areas where research seems to be necessary. The initial preparatory stage of manpower, the mechanisms of the short and long-run allocation of manpower encompass three important aspects that future research activities must cover. ** This paper was presented at the First Meeting of the Canadian Industrial Relations Research Institute, held at McGill University, July 6th, 1964.